2017
DOI: 10.1128/aem.03327-16
|View full text |Cite
|
Sign up to set email alerts
|

Spread from the Sink to the Patient: In Situ Study Using Green Fluorescent Protein (GFP)-Expressing Escherichia coli To Model Bacterial Dispersion from Hand-Washing Sink-Trap Reservoirs

Abstract: There have been an increasing number of reports implicating Gammaproteobacteria as often carrying genes of drug resistance from colonized sink traps to vulnerable hospitalized patients. However, the mechanism of transmission from the wastewater of the sink P-trap to patients remains poorly understood. Herein we report the use of a designated hand-washing sink lab gallery to model dispersion of green fluorescent protein (GFP)-expressing Escherichia coli from sink wastewater to the surrounding environment. We fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
128
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 150 publications
(154 citation statements)
references
References 39 publications
16
128
2
Order By: Relevance
“…These devices are more and more frequently described as reservoirs for pathogens and multidrug-resistant bacteria in both hospitals and domestic environments (21)(22)(23). Moreover, aerosolization and crosstransmission of pathogens from siphons have been demonstrated in recent carefully designed experimental studies (24,25). Our results reinforced recommendations to CF patients for home cleaning that should be targeted to the bathroom, kitchen, and other wet sites, with particular emphasis on wastewater drains, including hidden drains in domestic appliances.…”
supporting
confidence: 80%
“…These devices are more and more frequently described as reservoirs for pathogens and multidrug-resistant bacteria in both hospitals and domestic environments (21)(22)(23). Moreover, aerosolization and crosstransmission of pathogens from siphons have been demonstrated in recent carefully designed experimental studies (24,25). Our results reinforced recommendations to CF patients for home cleaning that should be targeted to the bathroom, kitchen, and other wet sites, with particular emphasis on wastewater drains, including hidden drains in domestic appliances.…”
supporting
confidence: 80%
“…A recent study by Kotay et al experimentally showed the ease with which E. coli can disperse from a sink after seeding (61). We also detected other CPOs in sinks and housekeeping closets that were highly related to patient isolates, but an epidemiological link could not be established.…”
Section: Discussionmentioning
confidence: 49%
“…Dampness has also been extensively studied in relation to the exacerbation of asthma symptoms [122], and these efforts are not repeated in this review. Motile Escherichia coli are capable of traveling from sink traps back up the drain into the sink, at a rate of 2.5 cm per day, from where they spread to other areas via droplet spray during sink use [123]. Similarly, water heaters host bacterial communities which can spread Mycobacterium via aerosolization at faucets and showerheads [124][125][126], and Legionella pneumophila can persist in building ventilation systems and infect building occupants [127,128].…”
Section: Moisture and Relative Humiditymentioning
confidence: 99%